Transposed intrathoracic stomach: Functional evaluation - Vishesh Jain; Shilpa Sharma; Rakesh Kumar; S K Kabra; Vidyut Bhatia; Devendra K Gupta (Wolters Kluwer Medknow Publications, 2012)
Background: To study the functional aspects of the transposed stomach in the thoracic cavity and its effects on other organ systems. Patients and Methods: Children who had undergone gastric transposition more than 5 years ago were evaluated for symptoms, anthropometry, anaemia, duodenogastric reflux, pulmonary function, gastric emptying, gastric pH, gastroesophageal reflux and stricture, gastric motility, and gastritis and atrophy on histological examination of gastric mucosa. Results: Ten children were evaluated at a median follow-up of 90.5 months. On evaluation of symptoms, nine children were satisfied with the overall outcome. All patients had their weight and 7 patients had height less than 3 rd percentile for their respective age. Anaemia was present in 7/10 children. On evaluation with hepatobiliary scintigraphy, duodenogastric reflux was present in only 1 patient. Mass contractions of the transposed stomach were present in two thirds of the children. The mean gastric emptying t1/2 was 39.1 minutes. Pulmonary function tests were suggestive of restrictive lung disease in all the patients. Forced vital capacity (FVC) and forced expiratory volume in 1 sec (FEV1) were worse in children who underwent transposition or diversion following oesophageal anastomotic leak. Acid secretion was preserved in most patients with episodes of high gastric pH during sleep in nearly half. Mild gastritis was present in all patients where as mild atrophy of the gastric mucosa was observed in only 1child. Helicobacter pylori were positive in 3/ 8 children. Barium swallow demonstrated reflux in 2 children. Conclusions: Most children with transposed stomach remain asymptomatic on follow up. However, subclinical abnormalities are detected on investigations, which need close observation as they can manifest later in life.